International studies of school design - lessons for Europe on innovation and risk - Deppeler, J; Thompson, I; Corrigan, D (SAGE Publications, 2021)
This editorial sets out the context and agenda for this special issue of European Educational Research Journal, which brings together five accounts of research from diverse international contexts in relation to schools that are being designed and promoted as innovative learning environments (ILEs). The overall purpose is to advance what is known about innovation and the challenges and risks involved for those engaged in the design and occupation of ILEs. We begin by outlining some of the important considerations for researchers working in ILE projects that specifically place an emphasis on participatory approaches to innovation and put educational and social change, at the centre of the work. We then highlight some themes for readers to keep in mind as they consider the arguments developed in the papers.